Pengaruh E-Wom (Electronic Word Of Mouth) Terhadap Keputusan Pembelian Produk Food & Beverage Secara Online Pada Marketplace Tokopedia - Ardi Noviandi (Business and Enterpreneurship Journal (BEJ), 2021)
Electronic Word Of Mouth has become one of the important factors needed by consumers to decide on an online purchase. This study was conducted to determine the effect of e-Wom (electronic word of mouth) on online purchasing decisions for Food Beverage products in the Tokopedia marketplace. The type of data used in this study is quantitative data where the data is recorded using numbers and classifications or information obtained from the distribution of questionnaires, then the data is processed using the SmartPLS3 application. The results of the study found that the variables (intensity, valence of opinion, and content) of e-WOM had a positive and significant influence on purchasing decisions. Keywords : Electronic Word Of Mouth, purchasing decisions